2015
DOI: 10.1371/journal.pone.0132757
|View full text |Cite
|
Sign up to set email alerts
|

IRF6 Is Involved in the Regulation of Cell Proliferation and Transformation in MCF10A Cells Downstream of Notch Signaling

Abstract: IRF6, a member of Interferon Regulatory Factors (IRF) family, is involved in orofacial and epidermal development. In breast cancer cell lines ectopic expression of IRF6 reduces cell numbers suggesting a role as negative regulator of cell cycle. IRF6 is a direct target of canonical Notch signaling in keratinocyte differentiation. Notch is involved in luminal cell fate determination and stem cell regulation in the normal breast and is implicated as an oncogene in breast cancer. Notch activation is sufficient to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…In addition, previous studies showed that IRF6 is a downstream target gene of the NOTCH signaling pathway and induced by the NOTCH signaling pathway in breast cancer and keratinocytes (9, 31, 32). NOTCH signaling pathway has been reported to play critical roles in the development and progression of human cancers through regulating ZEB1 expression and EMT pathway (3338).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, previous studies showed that IRF6 is a downstream target gene of the NOTCH signaling pathway and induced by the NOTCH signaling pathway in breast cancer and keratinocytes (9, 31, 32). NOTCH signaling pathway has been reported to play critical roles in the development and progression of human cancers through regulating ZEB1 expression and EMT pathway (3338).…”
Section: Discussionmentioning
confidence: 98%
“…Our data suggest an interesting link between innate immune response and the normal epithelial differentiation program, which may be independent of immunity-related functions. This noncanonical role of interferons has been only in part investigated in the skin 27,28 and observed in the mammary gland 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Among the 42 overexpressed genes in our study, the majority (23 of 42) are associated with dysregulation of gene expression in one or more human cancers. These include, but are not limited to, FOSB [ 40 ], FOS [ 41 ], BMPR1B [ 42 ], WNT5A [ 43 , 44 ], PDPN [ 45 ], BMPER [ 46 ], IRF6 [ 47 ], and MYC [ 48 , 49 ]. Additionally, FOS, MYC, and PDPN have been shown to be overexpressed specifically in meningeal tumors [ 41 , 48 , 50 ].…”
Section: Discussionmentioning
confidence: 99%